2006
DOI: 10.1577/t05-318.1
|View full text |Cite
|
Sign up to set email alerts
|

Tag Return Estimation of Annual and Semiannual Survival Rates of Adult Female Blue Crabs

Abstract: Abstract.-Stock status of the blue crab Callinectes sapidus in Chesapeake Bay is determined by comparing current estimates of fishing mortality with biological reference points. Given the recent focus on blue crab conservation, there is a need to obtain reliable estimates of survival to compare with the biological reference points. A tagging program was initiated on the terminally molted, mature female component of the Chesapeake Bay blue crab stock to estimate annual and semiannual survival rates. Crabs were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…He calculated M by the approach presented here but concluded that the approach substantially overestimated M because of tagging effects, such as tagging-related mortality and tag loss. Lambert et al (2006) indicated that their study did not violate any of the assumptions of the Brownie models, which include these potential biases; we therefore believe the approach is appropriate for our situation. Kahn and Helser (2005) did not use data from a tagging study; rather, they used relative abundance data from a research survey and a catch-survey model to estimate u and Z.…”
Section: Methodsmentioning
confidence: 87%
See 4 more Smart Citations
“…He calculated M by the approach presented here but concluded that the approach substantially overestimated M because of tagging effects, such as tagging-related mortality and tag loss. Lambert et al (2006) indicated that their study did not violate any of the assumptions of the Brownie models, which include these potential biases; we therefore believe the approach is appropriate for our situation. Kahn and Helser (2005) did not use data from a tagging study; rather, they used relative abundance data from a research survey and a catch-survey model to estimate u and Z.…”
Section: Methodsmentioning
confidence: 87%
“…Whereas the indirect estimates reflect the entire life history of the animal and thus apply to the entire stock, the direct estimates are based on the results of Lambert et al (2006) and apply only to the adult female portion of the stock.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations